2020
DOI: 10.1002/ijgo.13370
|View full text |Cite
|
Sign up to set email alerts
|

Can pre‐eclampsia explain higher cesarean rates in the different groups of Robson's classification?

Abstract: Objective To evaluate the impact of pre‐eclampsia on cesarean delivery by using the Robson classification. Methods A retrospective cross‐sectional study including all women who delivered in a referral maternity hospital in southeast Brazil from January 2017 to February 2018. Women were classified into 1 of 10 Robson groups and then further subdivided into pre‐eclampsia (PE) and non‐PE (NPE) groups. Frequency of cesarean was determined for each group and compared by using χ2 and prevalence ratio. Results Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Those articles were read in full considering the inclusion and exclusion criteria were considered. Then, ten articles 10 11 12 13 14 15 16 17 18 19 were included in the present review. Figure 1 shows the inclusion flowchart.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those articles were read in full considering the inclusion and exclusion criteria were considered. Then, ten articles 10 11 12 13 14 15 16 17 18 19 were included in the present review. Figure 1 shows the inclusion flowchart.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 2,988 cases of preeclampsia were reported; the prevalence ranged from 2.31% 11 to 14.15%. 13 Seven studies 10 13 14 15 16 17 18 did not report the occurrence of eclampsia. In the other 3 studies that reported eclampsia, it ranged from 1.66% 19 to 6.19%.…”
Section: Resultsmentioning
confidence: 99%
“…Robson group 10 added 7.61% to the overall CS rate, illustrating a high number of risk pregnancies, mainly in the middle adolescent group of women. Sanchez et al proved that preeclampsia was associated with the occurrence of CS, owing to higher rates of CS in Robson groups 1, 5, and 10 [22]. We have identified preeclampsia and placental abruption as main indications for CS in Robson group 10, mainly in middle adolescence young mothers.…”
Section: Discussionmentioning
confidence: 51%
“…This finding is not surprising, given that prematurity and disease-related complications often require a prompt delivery route. [19] These diverse scenarios with severity and phenotypic heterogeneity suggest that PE may result from varied pathogenic pathways. [6,7] Aberrant angiogenesis and systemic inflammation are proposed to be implicated in endothelial dysfunction, being important mediators in PE etiopathogenesis.…”
Section: Discussionmentioning
confidence: 99%